Keputusasaan Tokoh Wanita Dalam Novel Little Bee Karya Chis Cleave - Muhammad Idham Yassin; Saprudin; Ramdan Sukmawan (Fakultas Sastra Universitas Nahdlatul Wathan Mataram, 2022)
This research is entitled The Despair of Woman Character in Chris Cleave’s Little Bee Novel. The purpose of this research is to reveal the characteristics that lead in woman characters and to present as despairing. Descriptive qualitative is the method which applied in the reseach, using data collection that have included reading and collecting methods, and though mymetic approach methodology. Based on (WHOStuart, 2007) theory, the factors affecting despair were classified into two part: (1) Predisposition Factors, such as (genetic), (physical health), (mental health), and (personality structure), (2) Precipitation Factors, such as (loss), (failure), (environment), (parent), (health), (history), and (life’s pressure). Depending on various related causative aspects, it was identified that perhaps the woman character had a few impact as someone who has experienced, according to Sudjiman (1988:22), the author found different consequent causes characteristics that have an impact on the despair suffered instead by main woman character, such us the character’s quality of reason and soul that distinguish it from other individuals.